Age and sickness absence: Testing physical health issues and work engagement as countervailing mechanisms in a cross‐national context. Issue 4 (3rd February 2022) - Shao, Yiduo; Goštautaitė, Bernadeta; Wang, Mo; Ng, Thomas W. H.
Abstract: Workforces are aging rapidly and older workers are typically assumed to take more sickness absence. However, the relationship between age and sickness absence is not well understood, as research has yielded mixed findings and has neglected broader societal factors that cascade to shape the age‐sickness absence relationship. To advance the literature, we adopted a resource‐based perspective and investigated the relationship between employee age and sickness absence as mediated by two countervailing mechanisms: physical health issues and work engagement. We also highlighted two country‐level boundary conditions (health expenditure per capita and labor force participation rate) for these mechanisms. We tested our hypotheses with two archival datasets. In Study 1, using a sample of 28, 553 employees from 35 European countries, we tested a multilevel model and found that age was positively related to the number of physical health issues, which in turn was positively associated with sickness absence. Country‐level health expenditure per capita was found to mitigate this relationship. We also found that age was positively related to work engagement, which was negatively related to sickness absence, and country‐level labor force participation rate strengthened this relationship. In Study 2, using a multi‐wave dataset ( N  = 304) from the Health and Retirement Study (HRS) in the United States, we found further support for the two hypothesized mechanisms (physical health issues and work engagement) between age and sickness absence. Our findings have cross‐national implications for understanding and managing sickness absence by helping workers stay healthier and be more engaged in the context of population aging.